2012
DOI: 10.1159/000336351
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Colonic Diverticular Hemorrhage: Japanese Multicenter Study

Abstract: Background and Aim: Diverticular hemorrhage is the common cause of lower gastrointestinal bleeding, and its incidence has been increasing in Japan. However, the exact cause of diverticular hemorrhage is not well understood. We investigated the risk factors for diverticular hemorrhage. Methods: We selected 103 patients with diverticular hemorrhage as cases and patients with colonic diverticulosis without a history of bleeding were selected as control subjects, exactly matched for age and gender. We collected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 16 publications
3
31
1
5
Order By: Relevance
“…We identified 74 patients of advanced age, mainly males, who presented several co-morbidities and use of multiple medications. The dimension and characteristics of this group are similar to previous studies with similar designs and objectives (8,12,17,(24)(25)(26). The high number of co-morbidities and subsequent medication is in accordance with patient age.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We identified 74 patients of advanced age, mainly males, who presented several co-morbidities and use of multiple medications. The dimension and characteristics of this group are similar to previous studies with similar designs and objectives (8,12,17,(24)(25)(26). The high number of co-morbidities and subsequent medication is in accordance with patient age.…”
Section: Discussionsupporting
confidence: 79%
“…Yamada et al (11), whilst studying risk factors for CDB, also reported that the proportion of bilateral diverticulosis was larger among patients with hemorrhage, and Faucheron et al (9) and Suzuki et al (8) stated that right-sided diverticula location was associated with a significant risk of bleeding, which was independent of age. Even though right-sided diverticula are less prevalent in the western population than left-sided ones (9), these results highlight the need to monitor patients with known right-sided diverticulosis closely and to alert clinicians to the greater risk of severe bleeding in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have reported an association between rebleeding and usage of NSAIDs and antiplatelet agents as well as the presence of comorbidities [21,22] . The use of aspirin or NSAIDs increases risk for CDB [20,22] and CDB recurrence [11,12,23] . The presence of diverticula on both sides of the colon is reported to be a risk factor for CDB [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al found recently that the percentage of patients with diverticula on both the right and left colon was significantly higher in the diverticular than in the non-diverticular bleeding group (p=0.0011). Multiple regression analysis identified only the diverticular location as being significantly linked to the risk of diverticular bleeding (p= 0.0021) [18].…”
Section: Colonoscopy and Diverticular Bleedingmentioning
confidence: 99%